Macromineral requirements for maintenance, body weight gain and pregnancy of daiy cows - Camisa Nova, Carlos Henrique Paiva (2021)
Macrominerals are essential to maintain healthy, high reproductive efficiency and performance of dairy cattle. Based on it, understanding the macromineral requirements are crucial to formulate diets to meet the needs of cows accurately. However, studies to predict macromineral requirements for pregnant dairy cows are scarce. Thus, the goal of this study was to set approaches to predict the macromineral requirements of pregnant crossbred Holstein x Gyr cows. 62 Holstein-Gyr crossbred cows were enrolled in this experiment. The cows were sorted into 3 different groups: pregnant, open, and reference cows. Two subgroups were formed both for pregnant and open cow groups, where, the first subgroup was submitted to ad libitum feed management and the second subgroup was submitted to the maintenance nutritional management (feed intake equals 1.15% of body weight). The pregnant cows were harvested at four different days of gestation: 140, 200, 240, and 270 days, as well as the open cows, were harvested at day 200, 240, and 270 of gestation of the pregnant group. Seven periods of 28 days were accomplished for total tract digestibility (122, 150, 178, 206, 234, and 262 days of gestation). Net requirements for maintenance, growth, and gestation were estimated as well as the retention coefficient and efficiency to use macrominerals for gestation. The net requirement for calcium, phosphorus, sodium, potassium, and magnesium were 13.4837, 8.3534, 10.0751, 45.8889, and 4.4436 mg/kg of empty body weight (EBW), respectively. Additionally, the retained coefficient for calcium, phosphorus, sodium, potassium, and magnesium were 0.6516, 0.7402, 0.4267, 0.5641 and 0.4211, respectively. The net requirement for gain showed statistical differences between pregnant and open cows for calcium and phosphorus. On the other hand, sodium, potassium, and magnesium did not present differences for gain between pregnant and non-pregnant cows. For calcium, the predicting models of gain for non-pregnant cows and pregnant cows were (/) = 0.2818 × 0.6202 × and (/) = 3.1319 × 0.1484 × , respectively. For phosphorus, the models of gain for open and pregnant cows were ( ) = 0.7669 × 0.3843 × and (/) = 2.4456 × 0.1435 × , respectively. The predicting models of gain for sodium were (/) = 0.0201 × 0.7219 × and (/) = 0.1597 × 0.3185 × for open and pregnant cows, respectively. For potassium, the models of potassium for open cows were (/) = 0.2178 × 0.3514 × and for pregnant cows was (/) = 0.7269 × 0.1191 × . About magnesium requirement for gain, the model for open cows was (/) = 0.0508 × 0.4163 × and for pregnant cows was (/) = 0.6170 × −0.0700 × . Predictions for gain for sulfur for non-pregnant and pregnant cows were = 0.1708 × 0.5185 , and = 1.2422 × 0.1333 , respectively. For gestation, the predicting model for calcium was (/) = 0.0125 0.02489 × . For phosphorus, the model was (/ ) = 0.0207 0.02049 × . On sodium the equation was (/) = 0.0588 0.0115 × . For potassium, the model for pregnancy was (/) = 0.0439 (0.0119 × ) . The magnesium model for pregnancy was (/) = 0.0021 (0.01748 × ) and sulfur for pregnancy was (/) = 0.0263 (0.0148 × ). Keyword: Girolando, Pregnancy; Dairy cattle; Nutrient requirements; Mathematical modeling.